Respostas metabólicas e inflamatórias em sessão do método Treinamento Corretivo Postural (TCP)® - Rodrigues, Carla Nascimento dos Santos (2019)
Corrective Postural Training (TCP) ® is a gymnastic method with variability of movements that aims at postural control, metabolic changes and improvement in the quality of life of its participants. However, few studies have analyzed the behavior of physiological and metabolic variables in relation to the acute session of the modality. Thus, the present study aimed to analyze the effects of a session of the method (TCP)® on the concentration of lactate, glycemia, lipid profile (Triglycerides (TG), Total Cholesterol (CT), Low Density Lipoprotein (LDL) (IL-6) and Tumor Necrosis Factor-alpha (TNF-α)) and Creatin Kinase (CK) in human serum. active and healthy men without prior method experience. Sixteen adult and active men underwent for 40 minutes procedure (TCP) ® session. Blood samples were collected pre- and post-intervention to perform the dosages of: CK, lipid profile and IL-6 and TNF-α. For glycemia and lactacidemia analysis, samples were collected before, during and immediately after the session. The data were analyzed using the statistical software IBM® SPSS®. Results are expressed as mean and standard deviation. Statistical comparisons were performed using a one-way ANOVA and Paired Test-t for parametric data, and Wilcoxon's test for non-parametric data, being considered significant p <0.05. The main results showed that the (TCP) ® evaluated session promotes maintenance in the glycemic levels and significant increases in blood lactate at times 20 and 30 'compared to time 40'. The variables CT and LDL increased immediately after the session. However, the changes were insignificant for fractions of HDL, TG and VLDL. In addition, changes were found for neutrophil and eosinophil concentrations immediately after the session. Finally, cytokines TNF-α and IL-6 were not altered immediately after the session; as well as levels of CK 24hs after the protocol was performed. Thus, it was concluded that the (TCP)® session evaluated presented moderate intensity with predominance of the oxidative system and non-strenuous metabolic stimulus. The session presented maintenance of glycemic levels and alterations in mean lactate levels in relation to the involved musculature. As for the inflammatory profile, the session presented low inflammatory grade and low muscle damage, which makes it a session option for the beginning of a training protocol or as a regenerative approach after strenuous efforts.